Tumour reoxygenation after intratumoural hydrogen peroxide (KORTUC) injection: a novel approach to enhance radiosensitivity - Nimalasena, Samantha; Anbalagan, Selvakumar; Box, Carol; Yu, Sheng; Boult, Jessica K. R.; Bush, Nigel; Howell, Louise; Sinnett, Victoria; Murphy, William; Yarnold, John; Robinson, Simon P.; Somaiah, Navita (BJC reports, 2024)
Background KORTUC (0.5% hydrogen peroxide (H 2 O 2 ) in 1% sodium-hyaluronate) releases cytotoxic levels of H 2 O 2 in tissues after intratumoural injection. High levels of tumour control after radiotherapy plus KORTUC are reported in breast cancer patients. Here, we use human xenograft models to test the hypothesis that oxygen microbubbles released post-KORTUC are effective in modifying the hypoxic tumour microenvironment. Methods and materials Pimonidazole and Image-iT™ Red (live hypoxia marker) were utilised to assess dose-dependent changes in hypoxia post-H 2 O 2 in HCT116 and LICR-LON-HN5 spheroids. Using a dual 2-nitroimidazole-marker technique and phospho-ATM we evaluated changes in hypoxia and reactive oxygen species (ROS) respectively, in HCT116 and LICR-LON-HN5 xenografts following intratumoural KORTUC. Results A significant reduction in Image-iT™ Red fluorescence was observed in spheroids 1 h post-H 2 O 2 at ≥1.2 mM, maintained at 24 h. Ultrasound demonstrated sustained release of oxygen microbubbles within tumours, 1 h post-KORTUC. Hypoxia markers demonstrated significant tissue reoxygenation in both models post-KORTUC and significantly increased phospho-ATM foci reflecting increased ROS production. Conclusion Intratumoural KORTUC represents a novel oxygen delivery method, which can be exploited to enhance radiation response. If efficacy is confirmed in the ongoing phase 2 breast trial it could improve treatment of several tumour types where hypoxia is known to affect radiotherapy outcomes.